Perlindungan Hukum Kreditor Pemegang Hak Tanggungan Terhadap Obyek Hak Tanggungan Yang Diletakkan Sita Jaminan (Analisis Putusan Pengadilan Negeri Jakarta Timur Nomor 321/PDT.G/2012/PN.JAKTIM Dan Nomor 211/PDT.G/2014/PN.JAK.TIM) - Antonius Bernardus Hadisantoso (Darma Cendika Catholic University, 2018)
The purpose of this study was to find out and analyze the legal protection of holders of liability rights to the placement of collateral seizures on objects of mortgages and legal remedies for holders of mortgage rights in the presence of collateral seizures on objects of mortgage rights. From the results of the study it is known: First, the UUHT has provided forms of legal protection for holders of mortgage rights, among others, giving a priority or prioritizing position (droit de preference); always follow objects that are guaranteed in the hands of whoever the object is (droit de suite); fulfill the principle of speciality and publicity so that it can bind third parties and provide legal certainty to interested parties; as well as easy and sure execution. So that it should be if the object of the dispute that has been burdened with mortgages should not be placed confiscated in order to ensure legal certainty in the implementation of the parate execution. Secondly, the Mortgage Rights Holder whose interests are harmed by the decision/determination of seizure guarantee can make a third party resistance (derdenverzet). The interests of creditor holders of mortgage rights are clearly disadvantaged due to the placement of seizure guarantees on the object of mortgage rights, because the holders of mortgage rights cannot carry out executions in the presence of seizure guarantees.